PENYUSUNAN RENCANA PRIORITAS PENGEMBANGAN KAWASAN INDUSTRI MEDAN MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (AHP) - Binsar Nommensen Hasiolan Nababan; Parapat Gultom; Esther S. M. Nababan (Universitas Sumatera Utara, 2013)
Analytical Hierarchy Process (AHP) is a decision making method on determining the priority alternative of any alternative. Application of AHP begins by making the hierarchy structure of the studied problem. The pair-wise comparison matrix is used to form a correlation in the structure. In this matrix, the weight of each criteria is determined by normalization of geometric mean from responder opinion. Normalized maximum eigen value and eigen vector will obtained from this matrix. In the process of performing the hierarchy weighting factor or evaluation factor, the consistency test must be conducted (CR < 0,100). Application of AHP in this study was to determine the priorities of the development plan KIM. The results of the AHP analysis found that the Container Depot is the first priority in developing KIM (18.4%), followed by a second priority Workforce housing (15.2%), and the latter Hospital (5.9%).